Regional boundary observability: A numerical approach - Zerrik, El Hassan; Bourray, Hamid; Boutoulout, Ali (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we review the concept of regional boundary observability, developed in (Michelitti, 1976), by means of sensor structures. This leads to the so-called boundary strategic sensors. A characterization of such sensors which guarantees regional boundary observability is given.
Keywords: observability; regional observability; regional boundary observability; boundary strategic sensors